Strategi Pengelolaan Hutan Kemasyarakatan KTH Maju Bersama Desa Air Tenam Kabupaten Bengkulu Selatan : Strategi Pengelolaan Hutan Kemasyarakatan KTH Maju Bersama Desa Air Tenam Kabupaten Bengkulu Selatan - Dwi Maryani; Gunggung Senoaji; Yurike Yurike (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
This study aims to determine the socio-economic characteristics of the members of the Maju Bersama KTH, the performance of the Maju Bersama KTH, the success rate of social forestry management in the Maju Bersama KTH IUPHKm and the strategy for managing social forestry in the Maju Bersama KTH IUPHKm in Air Tenam Village, Ulu Manna District, South Bengkulu Regency, Bengkulu Province. This study was conducted from October to November 2024 in the Maju Bersama KTH IUPHKm, Air Tenam Village, South Bengkulu Regency, Bengkulu Province. The assessment of KTH performance is in accordance with the regulation of the Minister of Environment and Forestry of the Republic of Indonesia number P.89 / MENLHK / SETJEN / KUM.1 / 8/2018. The analysis method used for socio-economic characteristics, performance assessment and success rate of KTH is a qualitative and quantitative descriptive method. While the strategy for managing social forestry in community forests is analyzed using SWOT. The results of the study showed that KTH Maju Bersama had an institutional management performance score of 205 (56.94%), area management of 131.28 (65.64%), and business management of 102.09 (23.20%), with a total score of 438.37 (48.60%), so it is included in the Madya (Good/Medium) class KTH. The success of social forestry management shows that the majority of respondents (78%) achieved the successful category. The position of the forest management strategy is in quadrant II with the Diversification strategy.